Pengaruh Latar Belakang Pendidikan Pondok Pesantren Modern terhadap Motivasi Belajar Bahasa Arab - Keysha; Hikmah Maulani; Tatang Tatang (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
Education, which cannot be separated from every human being, is an important thing that must be considered. In Indonesia, there are places or educational institutions that can be used as a source of achieving an education. One of the educational institutions in Indonesia is an Islamic boarding school. Pondok Pesantren, an Islamic educational institution, is often called an Arabic language laboratory because the use of Arabic in the boarding school environment is extreme. The researcher intends to examine the effect of the background of Islamic boarding school graduates on their motivation to learn Arabic. Researchers use descriptive qualitative methods in collecting data dan analyzing it. In addition, researchers also conducted literature studies as additional data or supporting data in this study. The results obtained in this study indicate a significant influence of education in Islamic boarding schools on motivation to learn Arabic.